ANALISIS KEMAMPUAN BERPIKIR KRITIS DAN KREATIF MATEMATIS SISWA SMP PADA MATERI SEGIEMPAT DAN SEGITIGA - Siti Suci Robiah; Deliane Rahmawati (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aims to determine the ability of students to think critically and think creatively in mathematics on the material of squares and triangles. This research was conducted on 39 students at one junior high school in the city of North Cimahi. This study uses nine items. The research method uses qualitative analysis, namely a case study to determine the achievement of indicators in both abilities, on the results of solving the questions that students are doing. The data collection technique in this study was a test question. The data is then analyzed to find out how much completeness and accuracy the students answered. This shows that students have difficulty understanding the meaning shown by the questions, so that students are wrong in determining the right solution to solve the problems contained in the questions. So that it gives the conclusion that the abilities possessed by students are still in the low category.